2018
DOI: 10.1016/j.omtn.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

miR-199a-3p Modulates MTOR and PAK4 Pathways and Inhibits Tumor Growth in a Hepatocellular Carcinoma Transgenic Mouse Model

Abstract: Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related death worldwide. Prognosis is poor, and therapeutic options are limited. MicroRNAs (miRNAs) have emerged as potential therapeutic molecules against cancer. Here, we investigated the therapeutic efficacy of miR-199a-3p, an miRNA highly expressed in normal liver and downregulated in virtually all HCCs. The therapeutic value of miR-199a-3p mimic molecules was assayed in the TG221 mouse, a transgenic model highly predisposed to the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 51 publications
4
84
0
Order By: Relevance
“…In addition, AAV-mediated miR-199a/b-3p delivery by a single tail-vein injection in patient-derived orthotopic mice showed increased miRNA levels in tumor tissue, together with reduced tumor size, demonstrating the efficacy and nontoxicity of AAV8 vector system for potential HCC gene therapy [46]. Findings here obtained with miR-199a-3p-based therapeutics agree with those reported in the TG221 mice, proving the reliability of these animal models and suggesting miR-199a-3p replacement as a promising therapeutic option for human HCC [19].…”
Section: Patient-derived Xenograft Micesupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, AAV-mediated miR-199a/b-3p delivery by a single tail-vein injection in patient-derived orthotopic mice showed increased miRNA levels in tumor tissue, together with reduced tumor size, demonstrating the efficacy and nontoxicity of AAV8 vector system for potential HCC gene therapy [46]. Findings here obtained with miR-199a-3p-based therapeutics agree with those reported in the TG221 mice, proving the reliability of these animal models and suggesting miR-199a-3p replacement as a promising therapeutic option for human HCC [19].…”
Section: Patient-derived Xenograft Micesupporting
confidence: 80%
“…Since an miR-221 TG mouse also displays miR-199a-3p constitutive downregulation, miR-199a-3p mimics were adopted by using two experimental protocols: DEN priming in 10-day newborn mice followed by three IP injections per week for three weeks at three or five months of age. Both protocols showed a decreased number and size of nodules in miR-199a-3p mimics treated group with an anticancer effect similar to that observed in sorafenib-treated mice [19]. A decrease of mTOR and PAK4 protein expression was observed in HCC specimens from miRNA mimics treated animals, confirming similar mechanisms of action observed in other preclinical models, as well as in human HCCs [3,46].…”
Section: Mir-221 Tg Mousesupporting
confidence: 78%
“…Because miR‐199a is the third most highly expressed miRNA in normal liver and its downregulation correlates with poor prognosis, Callegari et al investigated the tumor suppressive effects of miR‐199a using a transgenic mouse model of HCC. For their in vivo delivery experiments, they used lipid nanoparticles that were composed of 1,2‐dioleoyl‐sn‐glycero‐3‐phosphoethanolamine, 1,2‐dimyristoyl‐sn‐glycerol, methoxypolyethylene glycol, and linoleic acid at a ratio of 50:48:2, and demonstrated that miR‐199a exerted anti‐tumor activity against mouse HCC.…”
Section: Therapeutic Approaches Based On Mirna Regulationmentioning
confidence: 99%
“…[70][71][72] In addition to LNA-mediated suppression of miRNA, TS-miRNA replacement has been attempted using miRNA mimics, viral vectors expressing miRNA, and small compounds that regulate the endogenous expression of miRNA. 14,73,74 Because miR-199a is the third most highly expressed miRNA in normal liver and its downregulation correlates with poor prognosis, 75 Callegari et al 76 inhibition is also effective against other diseases. For example, miR-122 is a liver-specific miRNA that stimulates translation of HCV by interacting with the 5′UTR of the HCV genome.…”
Section: Ther Apeuti C Approache S Ba S Ed On Mirna Reg Ul Ati Onmentioning
confidence: 99%
“…Previous studies have reported that dysregulation of PAK4 expression contributes to the development and progression of various tumors [28,29]. Several studies have reported that PAK4 could be regulated by many miRNAs in various cancers, including miR-485 and miR-199a-3p [30][31][32]. In OSCC, PAK4 serves as a super enhancer-associated candidate oncogene and promotes the proliferation of OSCC cells [33].…”
Section: Discussionmentioning
confidence: 99%